211k views
3 votes
What is the solution to the equation 9(w - 4) - 7w = 5(3w - 2)?

User Satomacoto
by
5.3k points

1 Answer

2 votes

Answer:

w = -2

Explanation:

First you need to remove the parentheses (so distribute 9 through the parentheses)

9w - 36 - 7w = 15w - 10

next you need to collect the like terms

2w - 36 = 15w - 10

then you need to move the terms (so move the variable to the left and change its sign)

2w - 15w = -10 + 36

then you need to collect the like terms and calculate

-13w = 26 (divide both sides by -13)

w = -2

User Ilya Kisil
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.